Diverse archaeal community of a bat guano pile in Domica Cave (Slovak Karst, Slovakia) - Chroňáková, Alica; Horák, Aleš; Krištůfek, Václav; Elhottová, Dana (Folia microbiologica, 2009)
The molecular diversity of Archaea in a bat guano pile in Cave Domica (Slovakia), temperate cave ecosystem with significant bat colony (about 1600 individuals), was examined. The guano pile was created mainly by an activity of the Mediterranean horseshoe bat (Rhinolophus euryale) and provides a source of organic carbon and other nutrients in the oligotrophic subsurface ecosystem. The upper and the basal parts of guano surface were sampled where the latter one had higher pH and higher admixture of limestone bedrock and increased colonization of invertebrates. The relative proportion of Archaea determined using CARD-FISH in both parts was 3.5-3.9 % (the basal and upper part, respectively). The archaeal community was dominated by non-thermophilic Crenarchaeota (99 % of clones). Phylogenetic analysis of 115 16S rDNA sequences revealed the presence of Crenarchaeota previously isolated from temperate surface soils (group 1.1b, 62 clones), deep subsurface acid waters (group 1.1a, 52 clones) and Euryarchaeota (1 clone). Four of the analyzed sequences were found to have little similarity to those in public databases. The composition of both archaeal communities differed, with respect to higher diversity of Archaea in the upper part of the bat guano pile. High diversity archaeal population is present in the bat guano deposit and consists of both soil- and subsurface-born Crenarchaeota.
Keywords: financování organizované; Animals; biodiverzita; ribozomální DNA; feces; Feces; DNA, Ribosomal; Chiroptera; RNA, Ribosomal, 16S; Slovakia; Molecular Sequence Data; DNA archebakterií; Archaea; Financing, Organized; Phylogeny; molekulární sekvence - údaje; Biodiversity; DNA, Archaeal; ekosystém; Ecosystem; Slovenská republika; zvířata; fylogeneze; RNA ribozomální 16S